Health Management and Innovation in the Organization of Brazilian Unified Health System Services - Helenitta Melo da Silva Alves; Suzana Santos da Costa; Gizely Rhose de Sousa; Cláudio Eduardo Sousa Lima; Márcia Maria Ribeiro Vieira; Josefa Soares Cavalcante; Viviane da Silva Bessa; Glaucia Adriana Nunes Araújo; Jocilane Lima de Almeida Vasconcelos (RSV, 2026)
Health management represents a fundamental dimension for the organization, sustainability, and effectiveness of healthcare systems, particularly within universal systems committed to equity and comprehensive care. In Brazil, the Unified Health System (SUS) has developed as one of the largest public healthcare systems worldwide, requiring complex governance mechanisms to coordinate services, allocate resources, and respond to diverse population health needs. However, contemporary challenges such as demographic transitions, epidemiological changes, financial constraints, technological transformations, and increasing demands for quality improvement require new approaches to healthcare management. Innovation has become a central element in the transformation of healthcare organizations by promoting new models of service delivery, improved decision-making processes, digital solutions, and more integrated approaches to care coordination. Nevertheless, innovation within public health systems requires consideration of organizational culture, workforce capacity, institutional arrangements, and social objectives. In universal healthcare systems, innovation must not only increase efficiency but also strengthen accessibility, equity, and responsiveness to population needs. This academic essay analyzes the relationship between health management and innovation in the organization of SUS services, discussing the role of governance, organizational transformation, technological incorporation, and strategic planning. The manuscript explores challenges faced by healthcare managers and examines perspectives for developing more adaptive, integrated, and innovative management models capable of strengthening the effectiveness and sustainability of the Brazilian public healthcare system.